2014
DOI: 10.1124/dmd.114.060194
|View full text |Cite
|
Sign up to set email alerts
|

CYP3A5 Genotype Impacts Maraviroc Concentrations in Healthy Volunteers

Abstract: CYP3A5 plays a prominent role in the metabolism of maraviroc, an approved drug for human immunodeficiency virus (HIV)-1 treatment and a candidate for HIV-1 prevention. We studied the effect of the CYP3A5 genotype on pharmacokinetics of maraviroc and a primary CYP3A5-dependent metabolite of maraviroc denoted as metabolite 1 (M1). Volunteers were screened for health status and CYP3A5 genotype (wild-type allele *1 and dysfunctional alleles *2, *3, *6, and *7) to obtain 24 evaluable subjects in three groups (n = 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 52 publications
4
40
0
Order By: Relevance
“…This is consistent with recent data in human liver microsomes (HLMs) showing that the estimated CYP3A5 contribution to maraviroc metabolism in HLMs from wild-type CYP3A5 *1/*1 donors (homozygous functional allele) was 32% compared with only 2% in HLMs from CYP3A5 *3/*3 donors (homozygous dysfunctional allele) (Tseng et al, 2014). Lu et al (2014) also concluded that maraviroc may be underdosed in patients who are homozygous for the CYP3A5*1 allele, which includes nearly one-half of all black individuals (Xie et al, 2004;Abel et al, 2008;Lu et al, 2014). Lu and colleagues are the first to present results on the effect that the CYP3A5 genotype has on maraviroc pharmacokinetics (PK).…”
supporting
confidence: 81%
See 2 more Smart Citations
“…This is consistent with recent data in human liver microsomes (HLMs) showing that the estimated CYP3A5 contribution to maraviroc metabolism in HLMs from wild-type CYP3A5 *1/*1 donors (homozygous functional allele) was 32% compared with only 2% in HLMs from CYP3A5 *3/*3 donors (homozygous dysfunctional allele) (Tseng et al, 2014). Lu et al (2014) also concluded that maraviroc may be underdosed in patients who are homozygous for the CYP3A5*1 allele, which includes nearly one-half of all black individuals (Xie et al, 2004;Abel et al, 2008;Lu et al, 2014). Lu and colleagues are the first to present results on the effect that the CYP3A5 genotype has on maraviroc pharmacokinetics (PK).…”
supporting
confidence: 81%
“…Exposure-response analyses from the maraviroc phase 3 trials (MERIT and MOTIVATE studies) show a flat response with maraviroc C avg above 75-100 ng/ml (McFadyen et al, 2008;Jacqmin et al, 2013). Therefore, the exposures achieved in the homozygous wild-type CYP3A5 group as reported in the Lu et al (2014) study should be sufficient for virologic response given that the median (interquartile range) maraviroc C avg was 103 ng/ml (90-117). The maraviroc dose of 300 mg BID should provide near-maximal efficacy across the range of exposures when given in combination therapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[22] Nonetheless, not always the use of MVC supports its use as a therapeutic strategy. [23] In this case, MVC failed to demonstrate its efficacy to treat patients with rheumatoid arthritis in a randomized, double-blind placebo-controlled trial. Among the possible explanation might be that selective CCR5 antagonism could be insufficient to significantly improve the measures assessed in the study and that CCR5 may not be a relevant mechanism in the progression of this disease.…”
Section: Off-label Use Of Maraviroc In Clinical Practicementioning
confidence: 99%
“…Among the possible explanation might be that selective CCR5 antagonism could be insufficient to significantly improve the measures assessed in the study and that CCR5 may not be a relevant mechanism in the progression of this disease. [23] However, far from considering that this is not a useful therapeutic option in some diseases, we should wonder many questions. For example, are present other countervailing chemokines that would be now responsible for maintaining the damage?…”
Section: Off-label Use Of Maraviroc In Clinical Practicementioning
confidence: 99%